Gender-based Analysis of Differences in IDLE Activities (Undertaken by EFL Students) - Ni Putu Ristia Ayu Ningsih; I Putu Indra Kusuma; Putu Adi Krisna Juniarta (Pioneer: Journal of Language and Literature, 2022)
In recent years, there has been an increase in the availability of research on informal digital learning of English (IDLE); however, the significant difference between IDLE activities undertaken by male and female students was currently unexplained. The purpose of this study was to see if there was a significant difference between EFL male and female students' use of Informal Digital Learning of English (IDLE). This study used a quantitative approach with an ex-post-facto design to address the research goal. The questionnaire was distributed to 656 students (181 males and 475 females) from the English Language Education Department at an Indonesian public university. The questionnaire data was then analyzed using descriptive statistics and parametric statistics, specifically the independent sample t-test. As a result, the findings indicated that there was a statistically significant difference between male and female students' participation in IDLE activities. There were 6 significant items with p-values less than 0.05 (p<0.05) among the 24 items. As a result of the current study's findings, EFL male and female students perform differently in IDLE activities, in which, male students outnumbered females in 5 IDLE activities.